2020
DOI: 10.5430/ijhe.v9n4p116
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Experienced by Students Studying through Open and Distance Learning at a Higher Education Institution in Namibia: Implications for Strategic Planning

Abstract: Online learning remains one of the most powerful enablers and accelerators for realising higher education studies by enhancing teaching by means of innovative technologies and pedagogies. However, the success rate of students studying through Open and Distance Learning (ODL) remains very low. Therefore, institutions of higher learning in Namibia should continuously establish and assess the challenges affecting the students who opt to study via distance mode to devise strategies required to address such challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…This was motivated by the fact that previous scholars (e.g. Ilonga, Ashipala & Tomas, 2020) have reported that poor internet connectivity continues to be detrimental to e-learning efforts in Namibia.…”
Section: Demographic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This was motivated by the fact that previous scholars (e.g. Ilonga, Ashipala & Tomas, 2020) have reported that poor internet connectivity continues to be detrimental to e-learning efforts in Namibia.…”
Section: Demographic Datamentioning
confidence: 99%
“…Nevertheless, this would have significantly affected students' experience elearning as accessibility is an important variable that influences students' perceptions of e-learning (Alshehri, Rutter & Smith, 2019). A study by Ilonga et al (2020) among university students in Namibia established that students had to invest in faster internet devices and data so as to mitigate against the effects of slow loading pages.…”
Section: Theme 1 -E-learning System Accessibilitymentioning
confidence: 99%
“…The 4IR-Rs demand that academics, students, and administrators undergo refresher training. Such will help the above-mentioned groups to understand digital technologies based on their needs, drawing from both professional and societal needs (Ilonga, Ashipala, & Tomas, 2020).…”
Section: Knowledge-buildingmentioning
confidence: 99%
“…The discussions of social and discipline habits reveal a need for a neutral platform of habits created through the strengths of disciplinary and social habits. A new, emerging category of habits is personal or pragmatic habits, that may address the needs of individual students by drawing on the strengths of both the social and discipline habits (Czerniewicz, 2018;Ilonga, Ashipala, & Tomas, 2020;Khoza, 2013). Studies (Khoza, 2013;Khoza & Manik, 2015;Mpungose, 2018) are of the view that students should learn with the aim of finding and understanding their identities through relevant theories such as The Tree Three Rings Theory (TTTRT) (Khoza, 2013) and others, before they attempt to address discipline or societal needs, in order to have control over WhatsApp and other digital technologies.…”
Section: Habits That Emerge From Whatsapp Usagementioning
confidence: 99%